Management curriculum between theory and practice - Mesarić, Josip; Kuzic, Joze; Dovedan Han, Zdravko (2011)
The boom in business schools and schools of management in the European and world formal and informal educational area on the one hand and poor, sometimes even catastrophic, effects of managerial practice on the other hand, initiate the necessity to reviewing the existing general management curricula. Curricula of many educational institutions with long tradition in manage-ment education have undergone this process recently, as well as those institutions that have de-signed their curricula recently and under socio-economic conditions that were significantly dif-ferent from contemporary conditions. The analysis of general management curricula in twenty business schools and schools of management at bachelor level and twenty eight schools at gradu-ate and master level indicated that there is no generally accepted management curriculum. Fur-thermore, curricula have been developed in different contexts and from different starting points and different ends and means. By analysing general characteristics of managerial knowledge, we have researched curricula through some existing models and approaches to their development (curriculum as BOK to be transmitted, curriculum as a product, curriculum as development and process). Starting with specificities of managerial education and the approach to curriculum de-velopment, we have introduced a new model for curriculum design through multidimensional prism. This model can be used when analysing and revising the existing general management cur-ricula.
Projekt MZOS
Projekt MZOS
ENG